PENGARUH POLA ASUH ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA KELAS V SD NEGERI 040536 PARTIBI LAMA - Leoni A Haloho; Reflina Sinaga; Saut Mahulae; Darinda Sofia Tanjung (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the effect of parents’ parenting style on the students’ learning motivation at the fifth-grade level of SD Negeri 040536 Partibi Lama. The method used in the study was a survey with a quantitative research method. The sample in the study involved 22 students from class VA and 21 students from class VB. The data collection tool used to see the students' learning motivation was a questionnaire that has been tested for validation and reliability. Both classes were normally distributed because those showed 0.200 ≥ 0.05. Based on the correlation test, the calculation result was 0.667, which meant that the correlation value was strong. The significant test was carried out to test the hypothesis by comparing the value of tcount with ttable. The value of tcount was 5,726 while ttable was 2,020. Because tcount 5,726 ≥ ttable 2,020, thus Ha was accepted and H0 was rejected. Through the t-test, it could be concluded that there was a significant relationship between parents’ parenting style and students’ learning motivation at the fifth-grade level of SDN 040536 Partibi Lama Merek in Karo.